DNA three-way junction-actuated strand displacement for miRNA detection using a fluorescence light-up Ag nanocluster probe. Issue 12 (16th May 2019) - Zhang, Xue; Liu, Su; Song, Xiaolei; Wang, Haiwang; Wang, Jingfeng; Wang, Yu; Huang, Jiadong; Yu, Jinghua
Abstract : MiRNA detection is realized by DNA three-way junction-actuated strand displacement and a fluorescence light-up Ag nanocluster probe. Abstract : A rapid and label-free fluorescence biosensing strategy for highly sensitive detection of microRNA-122 (miR-122) has been developed by the combination of DNA three-way junction (TWJ)-actuated strand displacement and a fluorescence light-up Ag nanocluster (AgNC) probe. In the presence of target miR-122, the attachment of miR-122 to its complementary DNA results in the unblocking of the toehold and branch migration domains in the TWJ, activating the strand displacement reaction (SDR) accompanied by the proximity between the G-rich DNA probe and DNA–AgNC probe; thus a remarkably enhanced fluorescence signal of AgNCs can be obtained owing to the G-rich fluorescence enhancement mechanism. The results reveal that this biosensor exhibits superb specificity and high sensitivity toward miR-122 with a detection limit of 0.030 nM. In addition, the practicality of the biosensor is demonstrated by analyzing miR-122 in three cell lines with satisfactory results. Furthermore, by the utilization of the toehold-mediated SDR and DNA–AgNC conjugates, this proposed strategy offers the advantages of rapidness, convenience, low cost, and simplified operation without the need for biological labeling and the addition of enzymes. Thus, the constructed biosensor might provide a valuable and practical tool for detecting miRNA and the related clinical diagnosis and fundamental biomedicine research.